Cost‐effectiveness of two endovascular treatment strategies vs intravenous thrombolysis. (31st December 2012) - Bouvy, J. C.; Fransen, P. S. S.; Baeten, S. A.; Koopmanschap, M. A.; Niessen, L. W.; Dippel, D. W. J.
<x xml:space="preserve">Abstract</x> Objective To assess the cost‐effectiveness of endovascular treatment against intravenous thrombolysis (IVT) when varying assumptions concerning its effectiveness. Methods We developed a health economic model including a hypothetical population consisting of patients with ischemic stroke, admitted within 4.5 h from onset, without contraindications for IVT or intra‐arterial treatment (IAT). A decision tree and life table were used to assess 6‐month and lifetime costs (in Euros) and effects in quality‐adjusted life years treatment with IVT alone, IAT alone, and IVT followed by IAT if the patient did not respond to treatment. Several analyses were performed to explore the impact of considerable uncertainty concerning the clinical effectiveness of endovascular treatment. Results Probabilistic sensitivity analysis demonstrated a 54% probability of positive incremental lifetime effectiveness of IVT‐IAT vs IVT alone. Sensitivity analyses showed significant variation in outcomes and cost‐effectiveness of the included treatment strategies at different model assumptions. Conclusions Acceptable cost‐effectiveness of IVT‐IAT compared to IVT will only be possible if recanalization rates are sufficiently high (>50%), treatment costs of IVT‐IAT do not increase, and complication rates remain similar to those reported in the few randomized studies published to date. Large randomized studies are needed to reduce the uncertainty concerning the effects of endovascular treatment.